KESIAPAN SARANA DAN PRASARANA DALAM MENGIMPLEMENTASI KURIKULUM 2013 SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI PROGRAM STUDI TEKNIK OTOMOTIF JURUSAN TEKNIK KENDARAAN RINGAN (TKR) SEKABUPATEN LOMBOK TIMUR TAHUN AJARAN 2013/2014 - Agus Junaidi; Subagyo Subagyo (Universitas Sarjanawiyata Tamansiswa, 2014)
The objectives of the study were (1) to describe the readiness of learning facilities; (2) to know the weakness of learning facilities; and (3) to know ideal learning facilities in implementing curriculum 2013 at state vocational high schools of east Lombok among automotive study program students in the academic year 2013/2014. This study shows that (1) the learning facilities of state vocational high schools of east Lombok were good enough. Generally in implementing curriculum 2013, the learning facilities to support the learning practices of state vocational high schools of east Lombok among automotive study program students in the academic year 2013/2014 were good enough to support the teaching and learning process. (2) There were some practice media that had not been had by the state vocational high schools of east Lombok among automotive study program students in the academic year 2013/2014, such as timing light Diesel, Trainer AC, and Card Stand EFI. It was because the learning tools were so expensive, so that the schools had not been ready to buy those media to support the teaching and learning process. (3) The ideal learning facilities were the facilities that were enough for students ration number.Â